Public space in dispute. The case of the street access to the campus of the national university of comahue - Romina Valeria Schroeder (Boletín Geográfico)
The urban space bears profound transformations, which also lead to reformulations of public space in terms of ownership, access and use. The article introduces a process of reflection taking as an example the order that the Municipality of the city of Neuquén has effected to the National University of Comahue to open, for public purposes, the campus entrance. This street is analyzed as a special category within the public space, since although citizen makes a shared use, this street is within the internal boundaries of the Institution. Methodology includes in situ observation and an opinion poll which emphasizes mainly on the perception that the university community has about the changes that are being generating. The materialization of actions points out, in many cases, social, economic distance between the various actors and agents that are exerting appropriation of space; the result will be reflected eventually in shaping the city. Therefore, it is imperative that any intervention is carried out under a systemic view, from social, morphological and structural perspectives that allow understand, in depth, complex processes, with a long-term vision.